1996
DOI: 10.1590/s0101-81751996000300010
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização dos tipos celulares presentes na hemolinfa de larvas e ninfas de Rhipicephalus sanguineus (Latreille) (Ixodoidea, Ixodidae) em diferentes estados nutricionais

Abstract: ABSTRACT. ClIARACTER IZATION OF TIIE CELULAR TYPES PRESENT lN TII E IIAEMOLYMPII OF LARVAE AND NIMPHS OF RHlPlCEI'IIALUS SAN(;UINEUS(LATREILLE) (IXODOIDEA, Ixo-DIDAE) lN DIFFERENT NUTRITIONAL STAGES. With lhe purpose of characterize morphologically lhe hemocytes of larvae and nymphs 01' Rhipicephalus sanguineus on ditTerent nutritional phases, it was obtained sal1lples ofhaemolYl1lph were obtained by sectioning the forel egs and collecting lhe drop there formed. A fter dried, the samples were fixed by methanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Spherulocytes are less abundant cells in the hemolymph, however, in R. sanguineus they appear to be more abundant (Carneiro and Daemon, 1997; Feitosa et al, 2015). In the present study, these cells present spherules in the cytoplasm and less organelles corroborating with other studies with insects (Brayner et al, 2005) and tick (Sonenshine and Hynes, 2008).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Spherulocytes are less abundant cells in the hemolymph, however, in R. sanguineus they appear to be more abundant (Carneiro and Daemon, 1997; Feitosa et al, 2015). In the present study, these cells present spherules in the cytoplasm and less organelles corroborating with other studies with insects (Brayner et al, 2005) and tick (Sonenshine and Hynes, 2008).…”
Section: Discussionmentioning
confidence: 90%
“…Studies about R. microplus cellular morphology and ultrastructure are scarce; for this reason, hemocytes identification through light and transmission microscopy was based on other tick species and other arthropods (Carneiro and Daemon, 1997; Borovicková and Hypsa, 2005; Habeeb and El-Hag, 2008; Feitosa et al, 2015, 2018). Silva et al (2006) studies with light microscopy reported six hemocytes types in R. microplus hemolymph described as prohemocytes, granulocytes, plasmatocytes, spherulocytes, adipohemocytes, and oenocytoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies on the tick immune system are limited in identifying and quantifying hemocytes, or in characterizing antimicrobial peptides (Sonenshine 1991;Carneiro and Daemon 1996;Pereira et al 2001;Silva and Bittencourt 2006). The expression of four forms of defensin was observed in the intestine, fat body and reproductive tract of Ornithodorus moubata (Nakajima et al 2001(Nakajima et al , 2002.…”
Section: Immune System Of Ticksmentioning
confidence: 99%